The contribution of Amélia Americano Domingues de Castro (1920-2020) to Geography Didactics - de Oliveira Mello, Márcia Cristina [UNESP] (Universidade Federal de Goias, 2022)
The teacher-training course at the Faculty of Philosophy, Sciences and Letters (FFCL) of the University of São Paulo (USP) played an important role in the constitution of the history of Didactics of Geography in our country. From the select group of professors graduated at USP between the 1930s and the 1960s emerged a generation of brilliant geographers, among them Professor Amélia Americano Domingues de Castro (1920-2020), which we highlight. She graduated in 1940 and was hired in 1942 as a Didactics teacher, becoming a pioneer in the area. She stood out for introducing Jean Piaget's ideas, presenting some answers to questions about methodological orientation concerning the teaching-learning process. Her intellectual production certainly evidences the matrix characterized by the scholastic orientation of that time, which had countless variables, whose versions can still be investigated. In this sense, we present in the XIV National Meeting of Post-graduation and research in Geography a fair homage to Professor Amélia, through the disclosure of her legacy that influenced the pedagogical field and the discussions around the teaching of Geography.
La aportación de Amélia Americano Domingues de Castro (1920-2020) a la Didáctica de la Geografía
A contribuição de Amélia Americano Domingues de Castro (1920-2020) à Didática da Geografia
Keywords: Amélia Americano Domingues de Castro; Didactics of Geography; teacher-training course in Geography